EVALUATION OF A RADON AIR MONITOR IN THE MEASUREMENT OF RADON CONCENTRATION IN WATER IN COMPARISON WITH A LIQUID SCINTILLATION COUNTER. Issue 3 (30th April 2019) - Higuchi, Shoko; Kamishiro, Yuuki; Ishihara, Maki; Yasuoka, Yumi; Mori, Yasunori; Hosoda, Masahiro; Iwaoka, Kazuki; Tokonami, Shinji; Takahashi, Rikiya; Janik, Miroslaw; Muto, Jun; Nagahama, Hiroyuki; et al.
Abstract: The World Health Organisation (WHO) recommends that the concentration of radon in water should be no more than 100 kBq m −3 (100 Bq L −1 ) and the Codex Alimentarius Commission states that the limit of quantification (LOQ) of a method should be no more than one-fifth of this value. In this study, a degassing method with an RAD7 device was used to measure radon concentrations in water, compared to a liquid scintillation counter (LSC) method used as the reference, to investigate whether the numerical value of the LOQ of this method was more than 1/5 (20 kBq m –3 ) of 100 kBq m –3 . The degassing method with leak prevention was shown to reach a target value of 20 kBq m −3 or less under a relative humidity of 6% or lower in the chamber of the RAD7 device. Accordingly, the RAD7 degassing method with leak prevention can be used to accurately measure radon concentrations in water within the guidance level set out by the WHO.